Program Asistensi Mahasiswa Sebagai Wujud Nyata Pengabdian Di TK Aba Metro Pusat - Suryadi Suryadi; Helena Dm; Maurin Amelia H; Melina Melina; Putri Khoirunnisa (Prodi PGSD Unsultra, 2025)
The student teaching assistance program is a concrete implementation of the university's tri dharma, particularly in the field of community service, aiming to integrate students' academic learning with real-world educational contexts. This program was carried out by students of the Early Childhood Islamic Education (PIAUD) Study Program at UIN Jurai Siwo Metro in TK ABA Metro Pusat using a Service-Learning (SL) approach. This method enables students to engage directly in the teaching process and early childhood education management through three main stages: preparation and orientation, implementation and evaluation, and conclusion and reporting.The objective of this program is to develop students’ pedagogical competencies in designing instructional administration, conducting adaptive teaching practices, and participating in extracurricular activities that support holistic child development. The results demonstrate that students were capable of preparing Daily Lesson Plans (RPH), managing classroom learning activities, and initiating extracurricular programs such as dancing, coloring, and Qur’an memorization (tahfidz), all of which contribute to children's motor, creative, and spiritual development. In addition, regular evaluations by field supervisors (DPL) enhanced students’ reflective thinking in their teaching practices. In conclusion, the student teaching assistance program significantly enhances students’ academic and professional skills as prospective early childhood educators while also positively contributing to the partner institution through collaborative innovation and meaningful support in children's learning experiences.